SURVEI KECELAKAAN KERJA PADA PETUGAS KESEHATAN DI RUMAH SAKIT ISLAM KAB KARAWANG - Chaerani Tri Yuliana; Wieke Widhiantika; Jumaedi; Muhidin; Wendi Darmawan (Journal of Innovation Research and Knowledge, 2024)
This study aims to analyse the occupational health and safety levels at the Islamic Hospital (RSI) in Karawang Regency, focusing on the extremely low incidence of workplace accidents. Based on the data collected, workplace accidents at RSI Karawang Regency are almost non-existent, with a very low incident rate of around 0.01%. The most common types of accidents, such as sharp object injuries, physical injuries from medical equipment use, and chemical exposure, all show very low incidence rates. This success can be attributed to the implementation of strict safety protocols, ongoing training, and effective maintenance of medical equipment. The study demonstrates that RSI Karawang Regency has created a very safe working environment, which not only protects healthcare workers but also enhances the quality of healthcare services provided to the community. The recommendations include strengthening safety training, regular maintenance, and the implementation of new technologies to continuously improve safety standards in the hospital.